2020
DOI: 10.1093/ndt/gfaa146.lb002
|View full text |Cite
|
Sign up to set email alerts
|

Lb002illuminate-A, a Phase 3 Study of Lumasiran, an Investigational Rnai Therapeutic, in Children and Adults With Primary Hyperoxaluria Type 1 (Ph1)

Abstract: Background and Aims PH1 is a rare genetic disorder characterized by hepatic oxalate overproduction, leading to recurrent kidney stones, nephrocalcinosis, progressive kidney failure, and multiorgan damage from systemic oxalosis. There are no approved pharmacologic therapies for PH1. Lumasiran is a subcutaneously-administered investigational RNAi therapeutic that targets glycolate oxidase to reduce hepatic oxalate production. We report the first results from the six-month, double-blind period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…[ 36 ] Scientists showed that lumasiran achieved >50% silencing of urinary oxalate levels, leading to improvements in secondary endpoints such as plasma oxalate levels and preventing kidney failure and eventual multiorgan damage from systemic oxalosis, and resulting in an FDA‐approved drug treating primary hyperoxaluria type 1 (PH1). [ 38 ] Alnylam has two late‐stage drugs under development for amyloidosis and hemophilia as well as multiple early‐stage programs for alpha‐1 liver disease, hepatitis B infection, and complement‐mediated diseases, all of which utilize their enhanced stabilization chemistry (ESC)‐GalNAc platform. [ 39 ] Fitusiran, which works by targeting the antithrombin gene SERPINC1, has resulted in increased thrombin levels in patients with hemophilia A or B similar to levels found in healthy patients.…”
Section: Sirna and Mrna Can Be Systemically Delivered To The Liver In Humansmentioning
confidence: 99%
“…[ 36 ] Scientists showed that lumasiran achieved >50% silencing of urinary oxalate levels, leading to improvements in secondary endpoints such as plasma oxalate levels and preventing kidney failure and eventual multiorgan damage from systemic oxalosis, and resulting in an FDA‐approved drug treating primary hyperoxaluria type 1 (PH1). [ 38 ] Alnylam has two late‐stage drugs under development for amyloidosis and hemophilia as well as multiple early‐stage programs for alpha‐1 liver disease, hepatitis B infection, and complement‐mediated diseases, all of which utilize their enhanced stabilization chemistry (ESC)‐GalNAc platform. [ 39 ] Fitusiran, which works by targeting the antithrombin gene SERPINC1, has resulted in increased thrombin levels in patients with hemophilia A or B similar to levels found in healthy patients.…”
Section: Sirna and Mrna Can Be Systemically Delivered To The Liver In Humansmentioning
confidence: 99%
“…[140][141][142][143][144] This 2). 145,146 Glycolate is excreted by the kidneys but is highly soluble and not associated with a renal phenotype in GO-deficient (Hao1 knockout) mouse models. 147 Rare human cases of biallelic loss of function variants in HAO1 have also been characterized to have high serum and urine glycolate levels without a disease phenotype, endorsing the safety of an RNAi approach to GO.…”
Section: Novel Rnai Therapies For Primary Hyperoxaluriamentioning
confidence: 99%
“…146 Lumasiran effected a 53.5% reduction in 24 hour urine oxalate levels (95% confidence interval 62.3-44.8%) compared to placebo (mean reduction 11.8%) and 85% of patients achieved a urine oxalate excretion within 150% of the upper limit of the normal range 146. Furthermore, no serious adverse events were reported.…”
mentioning
confidence: 96%
“…Indeed, preliminary results from Illuminate-A trial (Table 1) showed a 65% reduction of UOx after 6 months of treatment. 18 Consequently, prolonged treatment might be necessary before reaching a nearly normalized situation. Another important consequence could be that the systemic involvement of oxalate, especially in patients on chronic dialysis, could take longer time to be cleared with this medication compared to liver transplantation.…”
Section: Management Of Ph1 Patients In the Era Of These New Treatmentsmentioning
confidence: 99%
“…Developing better tools to evaluate the systemic oxalate burden will help delineate the best timing for kidney transplantation to avoid oxalate deposition recurrence in the kidney allograft. Questions regarding these new treatments and the outcome of kidney allograft, Innovative treatments involved in clinical trials NCT03681184 -Main inclusion criteria : ≥ 6 years, eGFR ≥30 mL/min -Preliminary results: 65.4% reduction of 24 hr UOx at month 6; no serious adverse event reported 18 . Estimated completion date: May 2024…”
mentioning
confidence: 99%